GREEN BANKING IMPACT: MEDIATION OF GREEN IMAGE AND BANK TRUST ON BANK LOYALTY - Kartika Dewi; Yuanita Ratna Indudewi (Jurnal Performa)
With the accelerating impacts of climate change, global consumers have become more eco-conscious about how they spend their money. Businesses are now urged to implement sustainability initiatives in their operations, including banking institutions as they are a source of funding for every industry. Socially Responsible Investing (SRI) theory is the grand theory for this research. This research is conducted to investigate the effect of green banking practice (X) on bank loyalty (Y) through green image (Z1) and bank trust (Z2) as mediators. This is a quantitative research in which primary data was collected through online questionnaires with a 6-point Likert scale using the Google form platform. The purposive sampling method was used to collect 150 samples who met the predetermined criteria. The data obtained was then processed and analyzed using the PLS-SEM method on SmartPLS 4.0 software. The results showed that green banking practice positively affects green image, bank trust, and bank loyalty. For the mediating variables, while the green image has no significant effect on bank loyalty and does not act as a mediator in the relationship, bank trust was found to have a positive significant effect on bank loyalty and partially mediates the relationship.